1999
DOI: 10.1136/adc.81.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Hay fever, eczema, and wheeze: a nationwide UK study (ISAAC, international study of asthma and allergies in childhood)

Abstract: Objectives-To describe the prevalence of atopic symptoms in children throughout the UK. Method-A questionnaire survey of 12-14 year olds throughout England, Wales, Scotland, and the Scottish Islands using the international study of asthma and allergies in childhood (ISAAC) protocol. Results-A total of 27 507 (86%) children took part. Recent rhinoconjunctivitis was reported by 18.2%, with 6.2% reporting symptoms between March and September; 16.4% reported itchy flexural rash in the past 12 months. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 32 publications
4
63
3
1
Order By: Relevance
“…[1][2][3] The prevalence of asthma and allergies in some Western countries has reached alarming proportions, affecting more than onethird of children within the general population. [4][5][6] The prevalence rates of childhood asthma, allergic rhinitis, and eczema show geographical variation, but generally with an increase worldwide through the latter half of the 20th century. [7][8][9] Apart from a recent study done in Scotland, 10 which showed a flattening off of the trend, there is general agreement on the increasing prevalence of asthma and allergies in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The prevalence of asthma and allergies in some Western countries has reached alarming proportions, affecting more than onethird of children within the general population. [4][5][6] The prevalence rates of childhood asthma, allergic rhinitis, and eczema show geographical variation, but generally with an increase worldwide through the latter half of the 20th century. [7][8][9] Apart from a recent study done in Scotland, 10 which showed a flattening off of the trend, there is general agreement on the increasing prevalence of asthma and allergies in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] This trend might reflect changes in severity, changes in medical care practices, and changes in the diagnostic labeling of these disorders, as well as a true increase in prevalence. 11,12 Moreover, despite extensive research, [4][5][6][7][8][9][10][11][12][13] the specific causes of these increases have not been found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 NO. 18 We found five studies including 191 patients that reported deaths as a result of SCC, 547,585,[588][589][590] with an average of 9.1% of patients dying from their disease on pooled analysis (95% CI 1.4% to 22.8%; I 2 = 79%) 23,67,[70][71][72] ( Figure 43). The greatest proportion of deaths was observed in a study of advanced T4 tumours in which two of three patients with eligible SCCs died (66%, 95% CI 9.4% to 99.1%) 590 during a mean follow-up period of 14 months.…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
“…Not only is there a continuing increase in prevalence [3], but there is also concern about over-use of b-agonists, whether short-or long-acting, leading to subsensitization of the b receptors and the side effects of inhaled steroids, which are amplified in the many patients who have comorbid allergic problems such as hayfever and eczema. Indeed, based on the UK International Study of Asthma and Allergies in Childhood (ISAAC) study in 1995, 14.4% of the entire 12-14-year-old population has either hayfever, eczema or both in addition to asthma [4]. Finally, none of the pharmacotherapies hitherto available for the control of asthma have been shown to modify long-term natural history or to ever achieve a cure.…”
mentioning
confidence: 99%